The antibacterial activity of bacteriocin produced by Lactobacillus acidophilus isolates against sensitive reference strain Lactobacillus acidophilus R0052 and its stability to different pH, heating and storage temperatures: Najim Hadi Najim , Zuhair Ahmad Mohammed , Zina Saab khudhir - Najim, Najim Hadi (The Iraqi Journal of Veterinary Medicine, 2012)
Two isolates of Lactobacillus acidophilus were isolated from locally homemade soft cheese and identified in accordance with their main features as described by bergeys manual of determinative bacteriology .Agar well diffusion bioassay was used for the evaluation of antimicrobial activity of cell free supernatant (culture filtrates) of Lactobacillus acidophilus isolates against the sensitive strain Lactobacillus acidophilus R0052 and the diameter of the inhibition zone was proportional to the bacteriocin concentration. The antimicrobial activity of the bacteriocin was proportional to the reciprocal of the highest dilution factor producing a detectable zone of inhibition . The storage temperature of the crude bacteriocin had a significant(P˂ 0.01) effect on its potency against the sensitive strain .The potential of the antimicrobial activities of the crude bacteriocin that was stored for 10 days at refrigeration temperature (4°C) was significantly (P˂ 0.01) higher than that stored at room temperature. The antimicrobial effectiveness of the crude bacteriocin was heat stable and retaining 100% of its activity after its exposure to 60 °C & 80°C for 10 minutes .Boiling of the crude bacteriocin for 30 minutes had significantly (P˂ 0.01) decreased its potency to 0% .The potency of the crude bacteriocin was stable after four hours of exposure to both neutral (pH7) and acidic (pH4) conditions but was inactivated at alkaline (pH9) condition.